2019
DOI: 10.5194/aab-62-597-2019
|View full text |Cite
|
Sign up to set email alerts
|

Technological and nutritional properties of meat from female wild boars (<i>Sus scrofa scrofa</i> L.) of different carcass weights

Abstract: Abstract. The aim of this work was to assess the technological and nutritional quality of meat from female wild boars. The muscle samples – Musculus longissimus thoracis et lumborum (LTL) and Musculus semimembranosus (SM) – were taken from a total of 40 female wild boar after a hunt. Carcasses were allocated to five groups according to weight (group I – 30±5 kg; group II – 45±4.9 kg; group III – 60±4.7 kg; group IV – 75±5.2 kg; group V – 90±5 kg). Studies that have been carried out have shown that technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Borilova et al [27] in their study, give even higher cooking losses, measuring 36.74% in the meat from the shoulder and 37.08% in the meat from the leg. In the study of Kasprzyk et al [33] the cooking loss measured from 32.01 to 35.71% in the LTL muscle, and from 33.53 to 36.71% in the m. semimembransus. The measures of drip loss, free water and cooking loss are highly affected by the factors like the used method and muscle type, which are probably the major source of variability among the mentioned meat quality traits.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Borilova et al [27] in their study, give even higher cooking losses, measuring 36.74% in the meat from the shoulder and 37.08% in the meat from the leg. In the study of Kasprzyk et al [33] the cooking loss measured from 32.01 to 35.71% in the LTL muscle, and from 33.53 to 36.71% in the m. semimembransus. The measures of drip loss, free water and cooking loss are highly affected by the factors like the used method and muscle type, which are probably the major source of variability among the mentioned meat quality traits.…”
Section: Discussionmentioning
confidence: 97%
“…Compared to our study, Babicz et al [34] presented lower values of free water percentage, measuring 22.35-22.89% in the m. longissimus lumborum, and 22.10-22.35% in the m. adductor femoris from wild boar crosses with domestic breeds. While Kasprzyk et al [33] obtained the free water measurement in a range of 20.10-24.48% in the LTL, and 20.74-23.09% in the m. semimembranosus. The cooking loss values obtained in our study were optimal for the meat of the wild boar [6,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of some factors on wild boar meat has been studied, and the most significant are: (i) the available food in the hunting grounds which finally determines meat composition, outstanding fat and protein content. In this way, a higher fat content has been found in wild boar meat from fenced hunting grounds, in areas where cereals are supplemented and in cultivated forest compared to areas/hunting grounds where only natural food is available [25,31,32,[42][43][44]; (ii) age, as when compared to juveniles, meat from adults has higher content of fat and protein, and lower water content [33,43,44]; (iii) the carcass weight, as there is a positive correlation between the protein content and the carcass weight [34]; (iv) the hunting period, because it has been demonstrated that the highest content of intramuscular fat is reached in wild boar harvested in winter compared to spring and summer, probably owing to the higher amount of available food from cultivated crops [35]. Interestingly enough, sex has no significant effect on meat proximate composition [31], though a study [44] found that younger females generally showed a higher content of protein than males, and another one observed a higher content of protein in meat from males [12].…”
Section: Large Wild Gamementioning
confidence: 99%
“…When comparing the macronutrients content of wild boar meat to pork, the main difference is the lower fat and higher protein content of wild boar meat [25]. Thus, the mean values in pork loin are 4.6% for intramuscular fat and 21.4% for protein content [12,25,26,34,42,43]. One study has reported that the mean fat content of wild boar meat was 5.3%, being similar to pork [23].…”
Section: Large Wild Gamementioning
confidence: 99%